The effect of microorganisms combination as probiotics in feed for growth performance, gastric evacuation rates, and blood glucose levels of milkfish, Chanos chanos (Forsskal, 1775) - Siti Aslamyah; Zainuddin Zainuddin; Badraeni Badraeni (Jurnal Iktiologi Indonesia, 2022)
The use of combinations of microorganisms as feed additives can synergize to produce enzymes to help the digestive process of feed. This study aims to determine the best combination of microorganisms as probiotics in feeding on growth performance, gastric evacuation, and blood glucose levels of milkfish. Milkfish with an initial weight of 9.21±0.14 g, reared at a density of 20 fish in an aquarium measuring 50 x 40 x 35 cm3 containing 48 L of water with 20 ppt salinity and equipped with a recirculation system. The research design was Completely Randomized Design with five treatments, namely: control (feed without microorganisms), Bacillus sp. and Lactobacillus sp., Rhizophus sp. and Aspergillus sp., Saccharomyces sp. and Trichoderma sp., and Mixed microorganisms, Bacillus sp., Lactobacillus sp., Rhizophus sp., Aspergillus sp., Saccharomyces sp., and Trichoderma sp. During 50 days of rearing, the fish were given experimental feed three times a day at 07.00, 12.00, and 15.00 at 5% body weight. The results showed that the treatment significantly affected growth, feed efficiency, and hepatosomatic index. However, it did not affect milkfish's survival and liver and muscle glycogen levels. Absolute growth (30.79±0.87 g), relative growth rate (333.91±5.83%), biomass growth (615.76±17.48%), feed efficiency (57.26±0.39 %), and the best hepatosomatic index (0.99±0.01) were obtained in the mixed microorganism treatment, and mg/g, and muscle 5.45-5.72 mg/g. The gastric evacuation rate and the fastest peak and peak decrease in blood glucose levels were obtained in the mixed microorganisms treatment at 5 and 3-4 hours postprandial. The diverse microorganisms can be added to the feed at a dose of 10 mL/kg to support the intensification of milkfish culture Abstrak Pemanfaatan kombinasi mikroorganisme sebagai aditif pakan dapat saling bersinergi menghasilkan enzim untuk membantu proses pencernaan pakan. Penelitian ini bertujuan menentukan kombinasi mikroorganisme terbaik sebagai probiotik dalam pakan terhadap kinerja pertumbuhan, laju pengosongan lambung, dan kadar glukosa darah ikan bandeng. Ikan bandeng dengan bobot awal 9,21±0,14 g dipelihara dengan kepadatan 20 ekor pada akuarium berukuran 50 x 40 x 35 cm3 yang berisi 48 L air bersalinitas 20 ppt dan dilengkapi sistem resirkulasi. Penelitian didesain dalam rancangan acak lengkap dengan lima perlakuan, yaitu: kontrol (pakan tanpa mikroorganisme), Bacillus sp. dan Lactobacillus sp., Rhizophus sp. dan Aspergillus sp., Saccharomyces sp. dan Trichoderma sp., serta kombinasi mikroorganisme Bacillus sp., Lactobacillus sp., Rhizophus sp., Aspergillus sp., Saccharomyces sp., dan Trichoderma sp. Selama 50 hari pemeliharaan, ikan diberi pakan percobaan 3 kali sehari yakni pukul 07.00, 12.00, dan 15.00 sebanyak 5% dari bobot badan. Hasil penelitian menunjukkan bahwa perlakuan berpengaruh nyata terhadap pertumbuhan, efisiensi pakan, dan indeks hepatosomatik. Namun, tidak berpengaruh terhadap sintasan, kadar glikogen hati dan otot ikan bandeng. Pertumbuhan mutlak (30,79±0,87 g), laju pertumbuhan relatif (333,91±5,83%), pertumbuhan biomassa (615,76±17,48%), efisiensi pakan (57,26±0,39%), dan indeks hepatosomatik (0,99±0,01) terbaik diperoleh pada perlakuan kombinasi mikroorganisme dan terendah pada kontrol. Kisaran sintasan yang dihasilkan 93,33-100%, glikogen hati 6,60-6,89 mg/g, dan otot 5,45-5,72 mg/g. Laju pengosongan lambung, serta mencapai puncak dan penurunan puncak kadar glukosa darah tercepat pada perlakuan kombinasi mikroorganisme pada jam ke 5 dan jam ke 3-4 post prandial. Untuk mendukung intensifikasi budidaya ikan bandeng, kombinasi mikroorganisme dapat ditambahkan dalam pakan dengan dosis 10 mL/kg pakan.